2020
DOI: 10.3390/ma13173906
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Waste Glass as an Activator in Class-C Fly Ash/GGBS Based Alkali Activated Material

Abstract: In this study, an alkaline activator was synthesized by dissolving waste glass powder (WGP) in NaOH-4M solution to explore its effects on the formation of alkali-activated material (AAM) generated by Class-C fly ash (FA) and ground granulated blast furnace slag (GGBS). The compressive strength, flexure strength, porosity and water absorption were measured, and X-ray diffraction (XRD) and scanning electron microscopy with energy dispersive X-ray (SEM-EDX) were used to study the crystalline phases, hydration mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In all samples containing glass, however, a raised background is visible, which may be caused by the presence of unreacted glass and the low degree of structural order of formed hydrated calcium silicates. Their structure may be similar to the C-S-H phase structure formed in natural conditions [45]. This confirms the observation that in the autoclaving process, the presence of reactive silica in the amorphous state increases the amount of the C-S-H phase, but at the same time, the transformation of this phase into a more stable form is hindered [46].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In all samples containing glass, however, a raised background is visible, which may be caused by the presence of unreacted glass and the low degree of structural order of formed hydrated calcium silicates. Their structure may be similar to the C-S-H phase structure formed in natural conditions [45]. This confirms the observation that in the autoclaving process, the presence of reactive silica in the amorphous state increases the amount of the C-S-H phase, but at the same time, the transformation of this phase into a more stable form is hindered [46].…”
Section: Resultssupporting
confidence: 85%
“…Instead, the most intense peaks from calcite were observed, which may indicate a significant degree of carbonation. This may be the reason for this sample's low compressive strength performance, where the calcium binder has carbonated instead of reacting with the silica [45,46]. In addition, due to quartz sand, very intense quartz peaks are observed in this sample.…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies showed that sodium silicate (Na 2 SiO 3 ) solutions are efficient activators for amorphous wollastonitic hydraulic binders (AWHs) [9]. However, the use of Na 2 SiO 3 can be challenging due to its corrosiveness [10] and significant environmental impact caused by its high embodied energy [11,12]. Hence, the production of a green, low-cost, and easy-to-use activator is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Sasui et al [11] synthesized an alkaline activator by dissolving waste glass powder in a 4 M NaOH solution and successfully enhanced the properties of class-C fly ash and ground granulated blast furnace slag. Moreover, they also reported that by increasing the amount of dissolved waste glass powder in the alkaline solution, a higher silicon concentration and increased reactivity were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Sasui et al used sieved WG powder dissolved in NaOH (4 M) solution in three different proportions, i.e., 10, 20 and 30 g per 100 mL of NaOH (4 M) solution to activate Class C fly ash/slag mixtures. The results showed that reactive Ca supplied from slag and the dissolved silica in the alkaline solution resulted in a homogeneous and compact matrix with low porosity and high mechanical strength [12]. Melele et al investigated reactive hardeners from rice husk ash and waste glass separately prepared by adding NaOH pellets, mixing with distilled water and stirring the solution for 30 min at 100 • C, to manufacture metakaolin-based geopolymer samples.…”
Section: Introductionmentioning
confidence: 99%